Richard Hooker, John Henry Newman A Via Media theology of the Eucharist - Curnow, Kelvin Fraser (2017)
The orthodox position that the Church of England represented a theological and ecclesiological Via Media between Roman Catholicism and Protestantism has been challenged in recent decades. Revisionist historians have disputed the view that the 16th-century apologist for the Church of England Richard Hooker presented the paradigm of an Anglican Via Media in his foundational works, Of the Lawes of Ecclesiastical Polity and Discourse on Justification. The disputes have centred on Hooker's doctrine of justification and theology of the Eucharist. Criticism has consequently been directed toward members of the 19th-century Oxford Movement who formulated their own contemporary religious Via Media based on the rediscovered works of Richard Hooker and 17th-century Anglican divines. Some historians also contend that no such Via Media existed and was fabricated by the Tractarians, particularly John Henry Newman, to suit their own theological ends. This article surveys the evidence which supports the case for the Via Media by examining Hooker's works for confirmation of the principle, and determining if Newman both identified and made use of the evidence accurately. The focus of this study will be comparing Eucharistic theology in the works of Hooker and Newman.
Keywords: Anglican; Calvin; Consubstantiation; Eucharist; John Henry Newman; Reformation; Richard Hooker; Transubstantiation; Instrumentalism